2017
DOI: 10.1080/16089677.2017.1378460
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of Lactobacillus casei on some biochemical parameters in diabetic mice

Abstract: Aims: Diabetes mellitus is a metabolic disorder characterised by inadequate pancreatic insulin secretion or the insulin present being unable to perform its function properly. Consistent with the beneficial effects of probiotics and their ability to lower glucose levels, an impact on diabetes treatment is also expected. The aim of this study was to evaluate the effect of Lactobacillus casei on various either biochemical parameters in a diabetic mice model. Methods: In the present study, 24 mice were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Carbon tetrachloride showed a significant increase in serum glucose level compared to control rats [66][67].Probiotichad insignificantdifference on glucose level compared to control .The obtained results came consistent with [68]found that probiotic treatment had no effect on blood glucose levels in healthy rats and [69]said that Lactobacillus caseidid not cause a significant change in blood gluose levels in control mice receiving the probiotic.…”
Section: Effect On Serum Glucose Levelsupporting
confidence: 69%
“…Carbon tetrachloride showed a significant increase in serum glucose level compared to control rats [66][67].Probiotichad insignificantdifference on glucose level compared to control .The obtained results came consistent with [68]found that probiotic treatment had no effect on blood glucose levels in healthy rats and [69]said that Lactobacillus caseidid not cause a significant change in blood gluose levels in control mice receiving the probiotic.…”
Section: Effect On Serum Glucose Levelsupporting
confidence: 69%
“…Lately, the biotechnological studies in the food industry domain have designed several commercial products that contained a single probiotic starter strain or a bacterial consortium. Furthermore, during recent years, it was thoroughly proved that the regular consumption of viable probiotics can determine a number of health benefits such as: a decreasing cholesterol level [13,14], anti-diabetic effect [15][16][17], alleviating diarrhea and constipation, improving the lactose intolerance and the human gut microbiome, in general [18,19], strengthening the immune system [20] or even antitumoral effects [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is one of the most important chronic metabolic disorders that is increasing rapidly in human societies in recent decades [1]. Today, this disease related to carbohydrate metabolism is divided into two main groups: type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%